84 A world record for life – a nationwide cpr initiative. (16th April 2018) - Mielke, A; Jensen, TW; Stark, N; Weber, P; Thomas, G; Lippert, F; Folke, F
Abstract : Aim: Bystander cardiopulmonary resuscitation (CPR) is a cornerstone of improving survival in out-of-hospital cardiac arrests (OHCA). 1 TrygFonden's World Record for Life aimed to show the public how easy it is to perform CPR by setting a world record in the number of people nationwide performing quality chest compression during 12 hours. Method: The record was set for 12 locations in Denmark over a 12 hour period on 22nd of May 2017. Each contribution was defined as 30 s of compression-only CPR on a Laerdal Q-CPR manikin with a Laerdal compression score of ≥65%. 2 Compression score was based on compression depth, rate, conflict of interest, hands-off time, and placement of hands. Data was stratified by citizens or by attendees at the Emergency Medical Services Congress 2017 (EMS2017) in Copenhagen, and analysed using Wilcoxon rank test. Results: Out of 6094 participants, 5707 (94%) reached a compression score 65% or more. Participants with a score of under 65% struggled with all components except compression rate compared to participants that reached 65%. Comparing laypersons and EMS2017-attendees, both groups performed within guidelines. The world record reached 12 different TV broadcasts, 11 radio broadcasts, 30 printed newspapers, and 41 web newspapers from 1 st to 26th May 2017. The world record had approximately 3, 739, 000 views on all platforms during the media coverage period. Conclusion: TrygFonden's World Record for Life showed an entire nation that untrained bystanders are able to provide effective CPR with 5707 reaching a compression score of 65% and 3, 739, 000 media views. References: . Rajan S, Wissenberg M, Folke F, Hansen SM, Gerds TA, Kragholm K, et al. Association of bystander cardiopulmonary resuscitation and survival according to ambulance response times after out-of-hospital cardiac arrest. Circulation2016;134(25):2095–104. . http://cdn.laerdal.com/downloads-test/f3784/Att_2_to_00021778.pdf Conflict of interest: None Funding: The project was funded by TrygFonden.